1997
DOI: 10.1046/j.1365-2141.1997.3313150.x
|View full text |Cite
|
Sign up to set email alerts
|

Survival of patients with chronic myelogenous leukaemia relapsing after bone marrow transplantation: comparison with patients receiving conventional chemotherapy

Abstract: Summary. Treatment with busulphan and/or hydroxyurea rarely produces remission in patients with chronic myelogenous leukaemia (CML) in chronic phase. HLA-identical sibling transplants almost always produce remission, and only about 20% of patients relapse post-transplant. The increased anti-leukaemic efficacy of transplants results from intensive pretransplant treatment and immune-mediated anti-leukaemia effects. We studied 433 patients surviving 5 2 years after diagnosis of CML to determine if patients who ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1999
1999
2003
2003

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…This issue has also been explored in chronic myelogenous leukemia. 19 Although every effort was made to obtain complete data including disease status of the patients, our study may have been limited by insufficient power to detect a difference in postrelapse survival between HD and NHL patients. Nonetheless, we have shown that relapsed patients may survive more than a few months after transplant and many can respond and even obtain remission with posttransplant therapy.…”
Section: Discussionmentioning
confidence: 99%
“…This issue has also been explored in chronic myelogenous leukemia. 19 Although every effort was made to obtain complete data including disease status of the patients, our study may have been limited by insufficient power to detect a difference in postrelapse survival between HD and NHL patients. Nonetheless, we have shown that relapsed patients may survive more than a few months after transplant and many can respond and even obtain remission with posttransplant therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Should this be the case, it may also facilitate a high response rate to DLI 3,4,6,7 and explain the slow pace of the disease after relapse following BMT. 14,15 Nonetheless, this hypothesis is not in contrast and does not rule out other possible explanations for the efficacy of DLI in CML.…”
Section: Discussionmentioning
confidence: 88%